The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4103/1755-6783.121013
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypokalemic quadriparesis in dengue fever

Abstract: Dengue fever is an acute mosquito-borne infection caused by dengue viruses belonging to the family Flaviviridae. It is an important public health problem in tropical and subtropical climates. Acute motor quadriparesis during the course of dengue infection is quite unusual and uncommonly reported. We hereby report two cases of acute motor quadriparesis during the course of dengue infection due to hypokalemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…dengue-related neurological presentation had been reported due to dengue-induced myelitis [6], hypokalemia [7], Guillain-Barre syndrome [8][9][10] and dengue myositis [11]. In our case, we believe that her symptoms resulted from a combination of spinal cord oedema and haemorrhage causing cord compression with concomitant denguerelated encephalitis and transverse myelitis.…”
Section: Similarmentioning
confidence: 64%
“…dengue-related neurological presentation had been reported due to dengue-induced myelitis [6], hypokalemia [7], Guillain-Barre syndrome [8][9][10] and dengue myositis [11]. In our case, we believe that her symptoms resulted from a combination of spinal cord oedema and haemorrhage causing cord compression with concomitant denguerelated encephalitis and transverse myelitis.…”
Section: Similarmentioning
confidence: 64%
“…4 Other authors have also reported few cases of motor quadriparesis following hypokamia in dengue fever. 5,6,7 In a large study from India, it was observed that neurological manifestations of dengue fever were present in two major categories, encephalopathy and pure motor quadriparesis but the quadriparesis was majorly due to myositis in that study. 8 Differential diagnosis for acute onset quadriapresis include: Acute Gullain barre syndrome, Acute flaccid paralysis in early pahse of myelitis, compressive myelopathy in spinal shock and channelopathies.…”
Section: Discussionmentioning
confidence: 78%